Punishment and modern society - Garland, David (iversity of Chicago Press, 1990)
An account of the role of punishment in modern society, building upon the work of Durkheim, Foucault, and others. It provides an interpretation of this complex social institution, showing how penal institutions interact with strategies of power, socio-economic structures and cultural sensibilities